Lesbian Fetishes, Queer Archaeology, and the Fusion of Baihe and Daomu in Explore Fictitious Tombs (Tanxuling). - Ni, Zhange (Chinese Literature & Thought Today, 2024)
In this article I analyze Explore Fictitious Tombs (Tanxuling), a web novel begun by JunSola in 2010 that fuses baihe (literally, "lily") and daomu ("tomb robbing") to exemplify genre mixing, an understudied phenomenon. Originally pronounced yuri in Japanese and used to designate a type of Japanese manga featuring female-female bonding, baihe has developed into a genre of Chinese Internet literature and tends to adopt fantastic settings for romance between women. As a genre of Chinese fantasy, daomu tells stories of archaeological adventures into the realm of magic and myths. In Explore Fictitious Tombs and other baihe-daomu novels, the female protagonists travel across China to excavate from ancient tombs artifacts and stories linked to the buried struggles of women desiring women. I read the protagonists as queer archaeologists working with lesbian fetishes, objects, or signs marking the return of a female completeness lost under patriarchy. Moreover, the narrative structure of the novel helps the reader to experience a queer temporality and envision an alternative Chinese history beyond the reproductive and heteronormative frame desired by global capitalism and the Chinese state. Finally, beyond its fictional world, Explore Fictitious Tombs is both a commodity not fully integrated into the capitalist political economy and a politically transgressive text circulating among queer women. The novel is a lesbian fetish translating/transcoding between sexuality and sociality and promoting in its readers a queer archaeological epistemology, a critical mindset devoted to excavating the suppressed and reconstructing the normalized.